Qiliqiangxin Capsules Optimize Cardiac Metabolism Flexibility in Rats With Heart Failure After Myocardial Infarction - Cheng, Wenkun; Wang, Lei; Yang, Tao; Wu, Aiming; Wang, Baofu; Li, Tong; Lu, Ziwen; Yang, Jingjing; Li, Yang; Jiang, Yangyang; Wu, Xiaoxiao; Meng, Hui; et al. (Frontiers in Physiology, 2020)
Metabolic modulation is a promising therapy for ischemic heart disease and heart failure. This study aimed to clarify the regional modulatory effect of Qiliqiangxin capsules (QLQX), a traditional Chinese medicine, on cardiac metabolic phenotypes. Sprague–Dawley rats underwent left anterior descending coronary artery ligation and were treated with QLQX and enalapril. Striking global left ventricular dysfunction and left ventricular remodeling were significantly improved by QLQX. Besides the posterior wall, QLQX also had a unique beneficial effect on the anterior wall subject to a severe oxygen deficit. Cardiac tissues in the border and remote areas were separated for detection. QLQX enhanced the cardiac 18F-fluorodeoxyglucose uptake and the levels and translocation of glucose transport 4 (GLUT4) in the border area. Meanwhile, it also suppressed glucose transport 1 (GLUT1) in both areas, indicating that QLQX encouraged border myocytes to use more glucose in a GLUT4-dependent manner. It was inferred that QLQX promoted a shift from glucose oxidation to anaerobic glycolysis in the border area by the augmentation of phosphorylated pyruvate dehydrogenase, pyruvate dehydrogenase kinases 4, and lactic dehydrogenase A. QLQX also upregulated the protein expression of fatty acid translocase and carnitine palmitoyl transferase-1 in the remote area to possibly normalize fatty acid (FA) uptake and oxidation similar to that in healthy hearts. QLQX protected global viable cardiomyocytes and promoted metabolic flexibility by modulating metabolic proteins regionally, indicating its potential for driving the border myocardium into an anaerobic glycolytic pathway against hypoxia injuries and urging the remote myocardium to oxidize FA to maximize energy production.